Towards the establishment of a permanent real time GPS tracking network for Dubai Emirate - 499935 Yousuf Abdelrahman Al Marzooqi; Abd. Majid A. Kadir; Fakulti Geoinformasi dan Harta Tanah (2004)
Thesis (Sarjana Sains (Kejuruteraan Geomatik)) - Universiti Teknologi Malaysia, 2004